A Wall Magazine of Postpartum Mothers' Health Literacy on Anemia at the Bangetayu Community Health Center, Genuk District - Nurjannah, Siti (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aimed to map the level of health literacy related to anemia among postpartum mothers at the Bangetayu Community Health Center, Genuk District, Semarang City, focusing on mothers’ knowledge, understanding, and awareness of anemia prevention and management during the postpartum period.Methodology: A descriptive quantitative study with a cross-sectional design was conducted involving 30 postpartum mothers selected through purposive sampling. Data were collected using a validated and reliable questionnaire consisting of 28 items assessing knowledge of postpartum anemia. Univariate data analysis was performed using SPSS version 21 to generate frequency distributions and percentages.Main Findings: The results showed that most postpartum mothers had a sufficient level of knowledge regarding anemia (76.7%), while 16.7% had good knowledge and 6.7% had poor knowledge. Respondents generally understood the definition, causes, and symptoms of anemia; however, misconceptions persisted regarding iron supplementation duration, nutritional sources of iron, and the long-term impact of anemia on maternal health.Novelty/Originality of this study: This study provides a structured health literacy mapping of postpartum mothers related to anemia at the primary healthcare level, which has rarely been explored in previous studies. The findings offer practical evidence to support the development of targeted, context-based health education interventions to improve postpartum anemia prevention and maternal health outcomes.